STUDI LITERATUR FAKTOR RISIKO YANG BERHUBUNGAN DENGAN KEJADIAN KANKER PAYUDARA PADA WANITA - Dewi Ayu Aprilianty; Rafidah, Rafidah; Suhrawardi, Suhrawardi; Rusmilawaty, Rusmilawaty (Jurnal Cakrawala Ilmiah, 2024)
The 2018 Global Cancer Observatory data from the World Health Organization (WHO) shows that the most cancer cases in Indonesia are breast cancer, which is 58,256 cases or 16.7% of the total 348,809 cancer cases. The results of the study regarding the incidence of female breast cancer varied (15-50%). Breast cancer (Breast Cancer / Carcinoma mammae) is a cancer that causes death because breast cancer can spread or move to surrounding tissues, spread to lymph nodes, enter blood vessels to other organs such as bones, lungs , liver / liver, and even the brain and cause malfunction of these organs that can cause death. The aim of the study was to determine the risk factors associated with breast cancer incidence in women. This study uses a literature study method from seven journals, namely 3 international journals and 4 national journals. This study uses bibliographic data analysis. The results of the study, based on literature review 7 journals, found that the incidence of breast cancer was (15 -% - 50%), the age at risk was (56.8% -72%), the length of time using hormonal contraceptives was at risk (34.2% -70, 8%), family history of suffering from breast cancer (15% - 77.1%). The results of statistical tests show that there is a relationship between age, duration of use of hormonal contraceptives, family history with the incidence of breast cancer in women. Advice for women to detect early independently with the Breast Self Examination method